Constitutional Labour Rights in Canada: Farm Workers and the Fraser Case - Fudge, Judy; Tucker, Eric; Faraday, Fay (Irwin Law, 2012)
On 29 April 2011, the Supreme Court of Canada released its much-anticipated decision in Attorney General of Ontario v Fraser, which dealt with the scope of constitutional protection of collective bargaining. The case involved a constitutional challenge to an Ontario statute on the grounds that it violated agricultural workers’ freedom of association and right to equality by excluding them from the statutory protection that is available to virtually all other private sector workers and by failing to provide them with alternative legislative support for meaningful and effective collective bargaining rights. Although the Court upheld the constitutionality of the legislation by an eight to one majority, it provided four different, and incommensurable, sets of reasons. For the union that instigated the litigation, Fraser is a defeat. For the labour movement and their advocates, Fraser is ambiguous. What is clear, however, is that the Supreme Court of Canada was badly divided over the scope of protection that freedom of association provides to the right to bargain collectively. This collection of original essays untangles the two stories that are intertwined in the Fraser decision—the story of the farm workers and their union’s attempt to obtain rights at work available to other working people in Ontario, and the tale of judicial discord over the meaning of freedom of association in the context of work. The contributors include trade unionists, lawyers, and academics (several of whom were involved in Fraser as witnesses, parties, lawyers, and interveners). The collection provides the social context out of which the decision emerged, including a photo essay on migrant workers, while at the same time illuminating Fraser’s broader jurisprudential and institutional implications. --Publisher's description
Keywords: Agricultural laborers; Canada. Arbeitsrecht. Verfassungsrecht; Canada. Collective bargaining; Canada. Employee rights; Canada. Freedom of association; Canada. Liberté d'association; Canada. Migrant agricultural laborers; Canada. Négociations collectives; Canada. Personnel; Canada. Travailleurs agricoles; Canada. Travailleurs agricoles migrants; Droit; Droits; Law and legislation; Legal status, laws, etc.